Synthesis and Performance Evaluation of Cellulose-based Slow-release Fertilizer: A Review - Dhyna Analyes Trirahayu; Ridwan P. Putra; Achmad Syarif Hidayat; Muhammad Iqbal Perdana; Erwina Safitri (KOVALEN: Jurnal Riset Kimia, 2022)
Cellulose-based materials are attractive candidates for the fabrication of sustainable and eco-friendly slow-release fertilizers. The ability of the cellulose structure to be modified and functionalized makes it promising as a scaffold backbone in the development of advanced agricultural materials. In this review, different synthesis techniques of cellulose-based slow-release fertilizers are discussed. Crucial parameters in the design of the slow-release fertilizers (i.e., slow-release behavior, water retention properties, and biodegradability) are presented. The applications of cellulose-based fertilizers in enhancing the growth of agricultural and horticultural commodities are provided. To date, solution polymerization is more widely employed in the preparation of cellulose-based slow-release fertilizers due to its low cost and simple operation, with no solvent recovery required. Esterification tends to be the most typical reaction during the synthesis of the fertilizers because of its high substrate solubility and more straightforward product purification. This review can be used as a reference to develop other efficient cellulose-based slow-release fertilizers that can be utilized to delay the release of fertilizers and prevent the overuse of fertilizers.